243 BLOOD PRESSURE REDUCTION LESS EFFECTIVELY REDUCES PLASMA C-REACTIVE PROTEIN IN PRIMARY HYPERTENSIVES WITH REDUCED GFR. (1st January 2006) - Rosario, R. F.; Simoni, J.; Khanna, A.; Wesson, D. E.
Abstract : Purpose: Post hoc analysis of a 7-year prospective study to determine predictors of GFR decline in primary hypertension suggested that increased plasma C-reactive protein (CRP) predicted lower survival and showed that CRP increased in those with reduced GFR despite systolic blood pressure (SBP) reduction. The present studies prospectively reduced SBP in primary hypertensives with elevated CRP to test the hypothesis that SBP reduction decreases CRP less effectively in subjects with reduced compared with preserved GFR. Methods: To recruit primary hypertensives that might have increased CRP, we identified those with macroalbuminuria [urine albumin (mg)-to-creatinine (g) ratio in a spot am specimen (alb/cr) > 200 mg/g Cr] because they have increased risk for cardiovascular disease (CVD) mortality. Primary hypertensives with preserved GFR had no clinical evidence of secondary hypertension or CVD and no diabetes and had calculated GFR (Cockcroft-Gault) > 90 mL/min. Primary hypertensives with reduced GFR additionally had no evidence of glomerulonephritis, had never received renal replacement therapy, and had GFR < 60 mL/min. SBP was reduced toward 130 mm Hg over 6 months. CRP and urine alb/cr were measured at entry and 6 months. Summary: Ten primary hypertensives (age 53.5 6 2.1 yr) with reduced GFR were compared to 8 with preserved GFR (age 54.8 6 1.9), all with macroalbuminuria. GFR was lower in the reduced compared to the preserved group (40.6 6 9 vs 101.4 6 7.5 mL/min p < .001) as by design. Entry CRP for 10 healthy, nonhypertensive, nondiabetic controls with GFR > 90 mL/min (6.7 6 0.6 mg/L) was higher than both hypertensive groups (p < .001). SBP was reduced similarly in hypertensives with reduced GFR (169 6 3 to 134 6 2 mm Hg) and with preserved GFR (151 6 3 to 135 6 2 mm Hg). SBP reduction was associated with decreased alb/cr in those with reduced GFR (276 6 27 to 202 6 32 mg/g Cr, p < .004, paired t) and preserved GFR (263 6 10 to 206 6 16 mg/g Cr, p < .002, paired t). CRP did not decrease in association with SBP reduction in those with reduced GFR (14.4 6 1.4 to 14.0 6 1.2 mg/L, p = .41, paired t) but did decrease in those with preserved GFR (13.8 6 0.9 to 12.4 6 0.5 mg/L, p < .02, paired t). Conclusions: The data show that SBP reduction less effectively reduces elevated CRP in primary hypertensives with reduced compared preserved GFR. The data suggest that in primary hypertension, factors associated with reduced GFR make BP reduction a less effective CVD risk reduction intervention than in those with preserved GFR.